A systematic review of the civilian airline industry: towards a general model of customer loyalty. (18th December 2019) - Bravo, Alencar; Vieira, Darli Rodrigues
Air transportation is an increasingly significant activity across the globe, and the industry is expected to grow, particularly with respect to civilian transportation. The issue of how companies can attract client loyalty in the face of the expected increase in airline routes is of particular interest. However, civilian air transportation is very diverse (e.g., in business models, areas of actuation); therefore, there is no universal model to predict loyalty that considers and encompasses the heterogeneity of civilian transportation. This paper uses a meta-analysis to solve this problem, systematically reviews the literature and collects data. Specific statistical concepts and tools are then used to interpret these data to provide generalisable results. The resulting model demonstrates meaningful relationships. The model is useful because it directs managers to concentrate their efforts on the most valuable elements needed to achieve customer loyalty and therefore sustain business.